AB0806 How Often Do Gout Patients Reach Target in A Rheumatology Practice?. (15th July 2016) - Corbett, E.; Pentony, P.; McGill, N.
Abstract : Background: Achieving the target serum urate has been repeatedly emphasized in published guidelines as a key determinant of successful gout management. Success rates are low in general practice and community audits but few studies have assessed results in a gout-orientated rheumatology practice Objectives: To determine the frequency of achieving target urate levels and the drugs required. Methods: Consecutive patients with gout who attended the private rooms between Jan 2010 and Sept 2014, in whom rheumatologist (NMcG) and patient agreed that urate-lowering therapy (ULT) was indicated and who commenced therapy were included. Serum urate targets: no tophus ≤0.36mmol/L; tophi ≤0.30mmol/L. Allopurinol was used initially. Due to limited access to febuxostat, for allopurinol intolerant patients with adequate renal function, probenecid was used next, then febuxostat. Results: Of 168 patients (148 male), 123 (83.1%) achieved target. The average;standard dev;range of serum creatinine were 98;31.9;21–231. Of patients able to tolerate allopurinol, 103/145 (71.0%) achieved target with an average dose of 393mg/day. Included in the 103 patients were 40 who did not achieve target on allopurinol 300mg/day, but did achieve target with a higher dose (400–900mg/day). For the remaining 42 of 145 patients, 35 were deemed to be non-compliant (did not attempt >3 dose increases or a change to another medication and failed to achieve target). For 7/145 patients, allopurinol was ineffective. 3/7 reached target on combination of allopurinol and probenecid. 2 did not increase beyond allopurinol 400mg/day and failed to reach target, 1 increased to allopurinol 900mg/day but failed to reach target, 1 changed to febuxostat 80mg/day without reaching target. 23/168 (13.7%) were unable to use allopurinol (due to concurrent azathioprine or intolerance). Of the 23, 8 reached target on probenecid, 1 on benzbromarone, 8 on febuxostat and 1 on combination of probenecid and febuxostat. 5 did not reach target (4 increased only to febuxostat 40mg/day, 1 attempted probenecid without reaching target and was unable to attempt febuxostat due to supply difficulties). Of 18 patients on probenecid (12 due to inability to use allopurinol), target was achieved by probenecid alone (7) or in combination with allopurinol (4) or with febuxostat (1). 2 attempted probenecid unsuccessfully, but then reached target on a retrial of allopurinol (1) or benzbromarone (1). Of 19 patients on febuxostat, target was reached on febuxostat alone (10) or on a combination of febuxostat and probenecid (1). 1 reached target on a re-trial of allopurinol, and 7 did not reach target. Of those 7, only 1 failed febuxostat 80mg daily, with 2 non-compliant and the others on febuxostat 40mg/day by end of the study period. In total (considering any ULT), 37/168 (22.0%) were non-compliant. No patient was intolerant or allergic to all ULTs. Conclusions: Even in a gout-oriented rheumatology practice, non-compliance was by far the commonest reason for not achieving the serum urate target. For compliant patients able to tolerate allopurinol, failure to achieve target was uncommon (4.8%). Although potent newer ULTs are of benefit in specific patients, if advances in ULT availability are going to have a major impact on overall treatment success, they will need to be associated with improved compliance. Disclosure of Interest: None declared